Vocational education and training in times of economic crisis : lessons from around the world - Pilz, Matthias [Herausgeber] (Springer International Publishing, 2017)
"This book brings together a broad range of approaches and methodologies relevant to international comparative vocational education and training (VET). Revealing how youth in transition is affected by economic crises, it provides essential insights into the strengths and weaknesses of the various systems and prospects of VET in contexts ranging from North America to Europe, (e.g. Spain, Germany or the UK) to Asia (such as China, Thailand and India). Though each country examined in this volume is affected by the economic crisis in a different way, the effects are especially apparent for the young generation. In many countries the youth unemployment rate is still very high and the job perspectives for young people are often limited at best. The contributions in this volume demonstrate that VET alone cannot solve these problems, but can be used to support a smooth transition from school to work. If the quality of VET is high and the status and job expectations are good, VET can help to fill the skills gap, especially at the intermediate skill level. Furthermore, VET can also offer a realistic alternative to the university track for young people in many countries." (Publisher, BIBB-Doku)
Keywords: S 2.3 Berufsbildungspolitik; G 1.3.2.2 Übergänge; I 2.2 Europa; I 2.3.4 Asien; I 2.3.2 Nordamerika; Berufsbildungspolitik; Berufsausbildung; Berufseinmündung; Jugendlicher; Arbeitsmarktchance; Internationaler Vergleich; Berufsbildung; Transfer; Europa; China; USA; Indien; Thailand; Bangladesch